STUDY OF THE CHEMICAL COMPOSITION OF PROCESSING INTEGRATED PRODUCTS MUD OF TAMBUKAN - H. G. Karagulov; E. F. Stepanova; S. B. Evseeva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Studies of quality of products of complex processing mud of Tambukan: press, alcohol and oil extrac-tions performed. The presence of humic acid and dehydrating the alcohol extraction of carotenoids and chloro-phyll in the oil alcoholic extraction of phytosterols in oil extraction using qualitative reactions, TLC, UV spec-trophotometry